(untitled) (Update Dental College Journal, 2013)
Background: Doxepin hydrochloride is a dibenzoxepin tricyclic, has a potent H1 & H2 receptor blocking actions. If topical doxepin can effectively control pruritus associated with eczematous dermatoses, we can use it as adjunctive therapy and can reduce the drawbacks of topical steroids and antihistamines. Methods: An interventional study from january 2010 to june 2010 has done in the department of dermatology and venereology, Faridpur Medical College Hospital, Bangladesh to evaluate the efficacy of topical doxepin cream in eczematous dermatoses. We included moderate to severe pruritic eczematous dermatoses patient in this study. Results: Improvement of pruritus was assessed at day 3 and at day 7 by both Visual analogue scale (VAS) and Itch severity scale (ISS). At day 3 by VAS 61.3 %( 57) patients showed improvement and at day 7 improvement rate increases to 84.9% (79). By ISS improvement at day 3 was 68.9% (64) and increased to 90.3% (84) at day 7. Improvement was experienced by all types of eczema patients. An average of 27.27% (29.88% by VAS and 24.65% by ISS) reduction of pruritus noticed at the end of day 3 and at the end of study, response increases to 55.58% (57.10% by VAS and 54.06% by ISS). Paired sample t test was done both for visual analogue scale (VAS) and itch severity scale (ISS) that compare the mean pruritus reduction at day 3 and day 7 with baseline pruritus (day-0). Pruritus reduction was statistically significant at day 3 and day 7 both by VAS & ISS. Conclusion: Doxepin cream is highly effective in relieving pruritus associated with eczematous dermatoses but it has little effect on eczema itself. DOI: http://dx.doi.org/10.3329/updcj.v2i1.13955 Update Dent. Coll. j: 2012; 2 (1): 14-20